Reafirmasi Posisi Dai dalam Dakwah Kolaboratif di Era Global - Syukri Syamaun (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This article aims to discuss the position of dai in the global context by examining their roles, challenges, and strategies for effective da'wah. Drawing from scholarly literature and case studies, this study highlights the importance of dai as educators, mediators, and community leaders. This article uses a qualitative approach through a